Temporal Trends and Predictors of Modern Contraceptive Use in Lusaka, Zambia, 2004–2011. (27th December 2015) - Hancock, Nancy L.; Chibwesha, Carla J.; Stoner, Marie C. D.; Vwalika, Bellington; Rathod, Sujit D.; Kasaro, Margaret Phiri; Stringer, Elizabeth M.; Stringer, Jeffrey S. A.; Chi, Benjamin H.
Abstract : Introduction . Although increasing access to family planning has been an important part of the global development agenda, millions of women continue to face unmet need for contraception. Materials and Methods . We analyzed data from a repeated cross-sectional community survey conducted in Lusaka, Zambia, over an eight-year period. We described prevalence of modern contraceptive use, including long-acting reversible contraception (LARC), among female heads of household aged 16–50 years. We also identified predictors of LARC versus short-term contraceptive use among women using modern methods. Results and Discussion . Twelve survey rounds were completed between November 2004 and September 2011. Among 29, 476 eligible respondents, 17, 605 (60%) reported using modern contraception. Oral contraceptive pills remained the most popular method over time, but use of LARC increased significantly, from less than 1% in 2004 to 9% by 2011 (p < 0.001 ). Younger women (OR: 0.46, 95% CI: 0.34, 0.61) and women with lower levels of education (OR: 0.70, 95% CI: 0.56, 0.89) were less likely to report LARC use compared to women using short-term modern methods. Conclusions . Population-based assessments of contraceptive use over time can guide programs and policies. To achieve reproductive health equity and reduce unmet contraceptive need, future efforts to increase LARC use should focus on young women and those with less education.